2015
DOI: 10.1039/c5ra05144d
|View full text |Cite
|
Sign up to set email alerts
|

Quaternary structures of GroEL and naïve-Hsp60 chaperonins in solution: a combined SAXS-MD study

Abstract: The quaternary structures of bacterial GroEL and human naïve-Hsp60 chaperonins in physiological conditions have been investigated by an innovative approach based on a combination of synchrotron Small Angle X-ray Scattering (SAXS) in-solution experiments and molecular dynamics (MD) simulations. Low-resolution SAXS experiments over large and highly symmetric oligomers are analyzed on the basis of the high-resolution structure of the asymmetric protein monomers, provided by MD. The results reveal remarkable diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 45 publications
2
14
0
Order By: Relevance
“…Although several GroEL crystallographic structures were released [5,4], they did not succeed in reproducing SAXS curves, and a new refined structure of GroEL in solution has been recently obtained by some of us, together with the one corresponding to naïve Hsp60 [6]. Hence, these structures refined at the atomic level were used to calculate the form factors P 1 (Q), P 7 (Q), and P 14 (Q) of GroEL and Hsp60 monomers and oligomers in solution.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Although several GroEL crystallographic structures were released [5,4], they did not succeed in reproducing SAXS curves, and a new refined structure of GroEL in solution has been recently obtained by some of us, together with the one corresponding to naïve Hsp60 [6]. Hence, these structures refined at the atomic level were used to calculate the form factors P 1 (Q), P 7 (Q), and P 14 (Q) of GroEL and Hsp60 monomers and oligomers in solution.…”
Section: Resultsmentioning
confidence: 97%
“…GroEL structure can be described as a large oligomeric protein containing 14 identical 57-kDa subunits, each one constituted by three domains: an apical domain (191-376 residues), an equatorial domain (1-133 and 409-548) and an intermediate domain and 377-408) [3]. Several GroEL crystallographic structures have been released in the form of a homotetradecamer, composed of two back-toback seven member rings [4,5], and a new GroEL structure has been recently redefined by some of us [6].…”
Section: Introductionmentioning
confidence: 98%
“…On the other hand, to exert its inhibitory activity, it is reasonable that the ligand could bind to the protein, also at the initial point of the folding cycle. For these reasons we have used a protein model recently built via homology modeling, starting from the crystal structure of the bacterial analogue chaperone GroEL in the absence of its co‐chaperone GroES (see pdb on supporting info) …”
Section: Resultsmentioning
confidence: 99%
“…Various studies, published over the past several years, have demonstrated new subcellular locations and functions for Hsp60, describing it as a ubiquitous molecule with multiple roles in health and disease [42][43][44]. Moreover, detailed studies of the structure of Hsp60 have been reported that help understand the functions of this multifaceted molecule [45,46].…”
Section: Hsp60mentioning
confidence: 99%